2015
DOI: 10.2967/jnmt.115.163527
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Response of Metastatic Merkel Cell Carcinoma to Targeted 177Lu-DOTATATE Therapy: Will PRRT Evolve to Become an Important Approach in Receptor-Positive Cases?

Abstract: This report illustrates an excellent partial response of Merkel cell carcinoma with multiple bilobar hepatic metastases to a single cycle of peptide receptor radionuclide therapy (PRRT) with 177 Lu-DOTA-TATE. This response, coupled with minimal side effects, warrants consideration of this therapy early in the disease course (rather than at an advanced stage after failure of other therapies) if the metastatic lesions exhibit adequate tracer avidity on somatostatin receptorbased imaging. Our patient showed progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…We found that 18 F-FDG and 68 Ga-somatostatin analogs provide good and equivalent diagnostic performance, with no significant differences either on a patient-based analysis or on a lesion-based analysis. From literature data, only few MCC patients have been imaged using both PET tracers, with better or equivalent performance of 68 Ga-SRI compared to 18 F-FDG PET/CT [ 25 27 ]; however, they are all case reports and, therefore, not reliably comparable with our findings. Similarly, our findings are not comparable with those reported by Lu et al [ 33 ] in the largest series of nine MCC patients who were investigated comparing 18 F-FDG PET/CT to 111 In-pentetreotide SRS.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…We found that 18 F-FDG and 68 Ga-somatostatin analogs provide good and equivalent diagnostic performance, with no significant differences either on a patient-based analysis or on a lesion-based analysis. From literature data, only few MCC patients have been imaged using both PET tracers, with better or equivalent performance of 68 Ga-SRI compared to 18 F-FDG PET/CT [ 25 27 ]; however, they are all case reports and, therefore, not reliably comparable with our findings. Similarly, our findings are not comparable with those reported by Lu et al [ 33 ] in the largest series of nine MCC patients who were investigated comparing 18 F-FDG PET/CT to 111 In-pentetreotide SRS.…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore, as shown by our data and reported in the NCCN guidelines [ 17 ], we retain that, in clinical practice, 18 F-FDG PET/CT should not be replaced by 68 Ga-SRI, which should be performed in addition, if clinically indicated. Anyway, it is important to consider that the decision on which tracer to employ at first line should be strongly influenced by the information that is considered more relevant for clinical management, in the perspective of “personalized medicine.” In this regard, 18 F-FDG PET/CT may also add prognostic information, as recently suggested [ 11 , 41 ], while 68 Ga-SRI PET/CT may be useful for both therapy planning and response assessment in a “theranostic strategy” when peptide receptor radionuclide therapy (PRRT) is considered as a further potential treatment option [ 24 , 25 , 27 , 35 , 42 ]. Moreover, with the advent of immunotherapy with immune checkpoint inhibitors, PET/CT imaging with the two different tracers may turn out to play a role in a tailored-treatment approach providing useful and complementary information also in the setting of response assessment and follow-up for advanced MCC [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In coordination with CT results, these findings provide opportunities for targeted radiotherapy to metastases . Therapeutic radioisotopes, such as the use of peptide receptor radionuclides as internal radiation therapy, have potential in MCC . Trials investigating radionuclides and peptide conjugated receptor analog delivery to neuroendocrine tumors for imaging and therapeutic purposes are ongoing.…”
Section: Discussionmentioning
confidence: 91%
“…[ 21 ] Furthermore, the metastatic lesions of MCC demonstrated avidity to both somatostatin receptors and (18)F-FDG, and an excellent partial response to a single cycle of peptide receptor radionuclide therapy with (177)Lu-DOTATATE is demonstrated, which may be reasonable as the first-line therapy for metastatic MCC. [ 22 ] The specific biomarkers of MCC include platelet-derived growth factor receptor, CD117, phosphoinositide 3-kinase, PD-L1, p63, vascular endothelial growth factor receptor, Ki-67, CD34, epithelial cellular adhesion molecule (Ep-CAM), nuclear factor kappa B, sonic hedgehog pathway proteins, and matrix metalloproteinase, which have been suggested to predict the prognosis of these patients. [ 2 ] Up to date, no effective systemic treatment for end stage MCC is available.…”
Section: Discussionmentioning
confidence: 99%